quiz1_sol - 1 a) Since X 1… X n are independent and...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 1 a) Since X 1… X n are independent and identically distributed (i.i.d.) N ( μ , σ 2 ) So, the joint distribution of X 1… X n is f ( x1 , … , x n ) = ∏ n i =1 f ( xi ) = ∏ n − ( xi − μ ) 2σ 2 2 e i =1 2π σ 2 Then, the likelihood function is, − ( xi − μ ) 2σ 2 2 2 L( x1 ,…, xn ) = Log{ f ( x1 ,…, xn )} = Log{∏ f ( xi ) = Log{∏ i =1 i =1 n n e 2πσ } n 1n 2 = − log(2πσ ) − 2 ∑ ( xi − μ )2 2 2σ i =1 Since σ 2 is known, we set Then, we get the maximum likelihood estimate of μ is, ∧ − 1n μ = x = ∑ xi # n i =1 b) Since X 1… X n are independent and identically distributed N ( μ , σ 2 ) , 1n ∑ xi E ( x ) = μ ,so n i =1 is still distributed normal distribution, and i 1n 1n 1n 1 E ( ∑ xi ) = ∑ E ( xi ) = ∑ μ = nμ = μ n i =1 n i =1 n i =1 n n 1n 1 1 Var ( ∑ xi ) = 2 Var ∑ xi = 2 n i =1 n n i =1 1 Var ( xi ) = 2 ∑ n i =1 n ∑σ 2 = n σ 2 i =1 n 1 So, the distribution of the estimate μ = x = 2 a) The trend components of B is a+bt ∧ − 1n σ2 xi is N ( μ , ) # ∑ n i =1 n The seasonal components of B is St # b) E ( xt ) = E (a + bt + st + yt ) = a + bt + st + E ( yt ) Since yt is stationary process with mean zero. So, E ( xt ) = a + bt + st The condition for stationary process is that E ( xt ) is independent of t, and cov( xs , xt ) = cov( xs + k , xt + k ) So xt is not stationary. # 3 a) cov( xt , xt + k ) = cov( zt + θ zt − 2 , zt + k + θ zt + k − 2 ) = cov( zt , zt + k ) + cov( zt ,θ zt + k − 2 ) + cov(θ zt − 2 , zt + k ) + cov(θ zt − 2 ,θ zt + k − 2 ) = cov( zt , zt + k ) + θ cov( zt , zt + k − 2 ) + θ cov( zt − 2 , zt + k ) + θ 2 cov( zt − 2 , zt + k − 2 ) If k=0, cov( xt , xt + k ) = cov( xt , xt ) = cov( zt , zt ) + θ cov( zt , zt − 2 ) + θ cov( zt − 2 , zt ) + θ 2 cov( zt − 2 , zt − 2 ) Since zt is i.i.d. Normal (0, σ 2 ) ⇒ cov( zt , zt ) = cov( zt − 2 , zt − 2 ) = σ 2 ⇒ cov( zt , zt − 2 ) = cov( zt − 2 , zt ) = 0 So, cov( xt , xt ) = σ 2 + θ 2σ 2 If k=1, cov( xt , xt + k ) = cov( xt , xt +1 ) = cov( zt , zt +1 ) + θ cov( zt , zt −1 ) + θ cov( zt − 2 , zt +1 ) + θ 2 cov( zt − 2 , zt −1 ) =0 Because of the independency of zt . If k=2 cov( xt , xt + k ) = cov( xt , xt + 2 ) = cov( zt , zt + 2 ) + θ cov( zt , zt ) + θ cov( zt − 2 , zt + 2 ) + θ 2 cov( zt − 2 , zt ) = θσ 2 If k=‐2 cov( xt , xt + k ) = cov( xt , xt − 2 ) = cov( zt , zt − 2 ) + θ cov( zt , zt − 4 ) + θ cov( zt − 2 , zt − 2 ) + θ 2 cov( zt − 2 , zt − 4 ) = θσ 2 For the other K’s, cov( xt , xt + k ) = 0 . So, γ (k ) = cov( xt , xt + k ) = { γ (k ) cov( xt , xt ) σ 2 + θ 2σ 2 θσ 2 0 k = ±2 k =0 other wise # b) ρ (k ) = ρ (k ) = { θ 1+θ 2 1 0 k = ±2 # k =0 other wise 4 γ (k ) = cov( xt , xt + k ) , for k ≥ 1 Plug the relation xt = φ xt −1 + ε t ⇒ xt + k = φ xt + k −1 + ε t + k into the above function, γ (k ) = cov( xt , xt + k ) = cov( xt , φ xt + k −1 + ε t + k ) = φ cov( xt , xt + k −1 ) + cov( xt , ε t + k ) = φ cov( xt , xt + k −1 ) = φγ (k − 1) = φ 2γ (k − 2) = = φ k γ (0) Since, ρ (k ) = γ (k ) , so γ (k ) = φ k # γ (0) ...
View Full Document

This note was uploaded on 08/08/2010 for the course AMS 316 taught by Professor Xing during the Fall '09 term at SUNY Stony Brook.

Ask a homework question - tutors are online